EFEKTIVITAS LEMBAR KERJA SISWA IPA TERPADU BERORIENTASI MODEL PEMBELAJARAN BERBASIS PENGALAMAN UNTUK MENINGKATKAN HASIL BELAJAR DITINJAU DARI SIKAP ILMIAH SISWA SMP - Prayunisa, Fena; Marzuki, Ahmad Dedi (LPPM Institut Pendidikan Nusantara Global, 2023)
The aim of the research was to select integrated science worksheets oriented towards an experience-based learning model, which is expected to foster a scientific attitude and improve student learning outcomes. Previous research has never applied LKS in science learning, namely a combination of LKS teaching materials and experience-based learning models. This research method is an experimental method with a quasi experiment with the matched only pretest-posttest control group design. This research was carried out at SMP N 1 Masbagik. Validation of the learning tools by 3 validators. Assessment and revision of the learning tools and instruments was carried out until the tools and instruments were suitable for application in experimental research. Then the learning process is carried out. The control group received treatment using a conventional LKS learning model, while the experimental group used an integrated science LKS learning model oriented towards an experience-based learning model. Data analysis uses the t test. After carrying out the posttest, there was a significant difference between the control class and the experimental class. The experimental class in the posttest had an average of 88.8, which initially had a pretest average of 64.6, while the control class had an average posttest result of 75.8, which initially had a pretest average of 64.8